Citius, Altius, Fortius: Global University Rankings as the “Olympic Games” of Higher Education? - Yudkevich, Maria; Altbach, Philip G; Rumbley, Laura E (International Higher Education, 2016)
The global university rankings can be seen as analogous to the Olympics. This article compares aspects of the Olympics to how global university rankings work, comparing medal counts to academic rankings.